Design and Development of Food Ordering and Management System for One Six Eight Restaurant - Ma Xiao Ting; Alduais, Nayef (Applied Information Technology And Computer Science, 2024)
Web-Based Ordering and Management System for One Six Eight Restaurant is developed due to several issues such as platform used can cause confusion on customers who placed order at the same time, human error on summarising large amounts of orders, and manual reporting can cause waste in time and materials. Thus, the aim of the proposed system is to transform the manual food ordering process into a systematic process where waterfall model methodology with structured approach is used in this study. Context Diagram (CD), Data Flow Diagram (DFD), and Entity Relationship Diagram (ERD) is conducted. Moreover, the proposed system is successfully developed using Hypertext Preprocessor (PHP) with the database My Structured Query Language (MySQL). Functional Testing and User Acceptance Test is done to check the system. The proposed system has achieved its aim where the system is able to improve the ordering process of One Six Eight Restaurant.